FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS TEMPE DI INDONESIA - Lindajati Tanuwidjaja; Hari Rom Hariyadi; Yetty Mulyati (Research Center for Chemistry - LIPI, 1991)
Field Sill dies all tempe home industries had been carried out ill 1975- 1976 and 1987, covering 25 tempe home industries ill West Java and Jakarta areas, 15 ill Central Java and Yogyakarta areas and 15 ill East Java. The quality and price of tempe samples collected from the visited industries and market varied considerably. The price of tempe. varied from Rp 400,-/Kg to Rp l.000,-/Kg in 1987, while the protein content varied from 14.8% to 22.7%. The variation in fat, carbohydrate, fiber and ash content was also observed. Variation was observed also in the use of raw mdterials, additives and inocula as well as variation ill tempe processing techniques, i.e. in the soaking, cooking and inoculation which had caused the variation in tempe quality